Synthesis and characterization of silver nanoparticles for photocatalytic application - B. Maheshkumar; Vismitha S. Patil; G. H. Nagaveni; Raghu M. Gunnagol; M. A. Gadyal; M. N. Kalasad (Hybrid Advances, 2025)
Metal nanocrystals have gained immense significance due to their unique physical, chemical and biological properties and widely used for catalysis, drug delivery, water purification, solar cells etc. In this study, synthesis of silver (Ag) nanoparticles by chemical precipitation method using thioglycolic acid (TGA) as a capping molecule. The size of the Ag nanoparticles 17–23 nm is controlled by varying the concentration of reducing agent. Optical and structural properties of the Ag nanoparticles are systematically characterized using optical absorption spectroscopy, photoluminescence spectroscopy, FTIR, X-ray diffraction (XRD) and transmission electron microscopy (TEM). FTIR analysis confirms the effective surface passivation of Ag nanoparticles by thiol molecules, while XRD patterns reveal face-centred cubic (fcc) crystal structure. The synthesized Ag nanoparticles served as potential catalyst in photocatalysis of an organic dye. The nanoparticles exhibit 92 % of degradation efficiency within 200 min towards the model pollutant methyl orange (MO) dye under mercury vapor lamp irradiation.